Analisis Kritis Penggunaan Konten Video Berbasis Kecerdasan Buatan dalam Pembelajaran IPAS di Sekolah Dasar - Lia Farida; Oki Sandra Agnesa; Sella Nofriska Sudrimo (YASIN, 2026)
The use of artificial intelligence (AI)-based learning media in elementary education continues to develop, but research discussing teacher validation of AI content and the digital literacy of elementary school students remains relatively limited. This study aims to analyze the use of AI-based learning videos in Natural and Social Sciences (IPAS) learning, examine teachers’ strategies in validating AI content, and describe the development of students’ digital literacy during the learning process. This study used a qualitative approach with a case study design involving one experienced IPAS teacher and 15 students of MI Muhammadiyah 2, Sorong Regency, Southwest Papua. Participants were selected through purposive sampling. Data were collected through semi-structured interviews, open-ended questionnaires, observation, and document analysis. The results showed that the use of AI-based learning videos was able to increase students’ learning interest, engagement, and understanding of cultural diversity material in IPAS learning. Students gave positive responses to the animated display, audio, and interactive visuals, which made learning more interesting and easier to understand. Nevertheless, some students experienced difficulty following the information because the video transitions were too fast and the visual details were unclear. This study also found that teachers play an important role in validating AI content before it is used in learning by comparing the video material with textbooks and various other official sources. In addition, the use of AI-based videos began to train students’ digital literacy through the ability to ask questions and re-question information obtained from digital media. The conclusion of this study affirms that AI-based learning videos can serve as innovative and interactive learning media in elementary schools when accompanied by active teacher guidance and an appropriate content validation process. These findings contribute to the development of AI integration and digital literacy practices in elementary education.